Food losses in agrifood systems: What we know - Delgado, Luciana; Schuster, Monica; Torero, Maximo (Annual Reviews, 2023)
In 2015, the United Nations and the G20 put food loss and food waste on the global agenda. While progress has been made since then, the scale of the problem persists because food loss and food waste are measured together, not separately. The paucity of data also poses a challenge. This article reviews the measurements, causes, and determinants of food loss as well as the interventions to reduce it. The review finds that food loss is considered in isolation, even though it is one of the causes and results of how agrifood systems function. The review calls for improved microdata collection and standardized measurements to separate food loss from food waste. Such efforts would help integrate feedback loops and cascading effects across the value chain with agrifood systems to identify intervention hot spots, trade-offs, and synergies of interventions as well as the effects of food loss reduction on socioeconomic, environmental, and food security goals.